The Influence of Tax Knowledge and Perception on Compliance With Pph 21 Tax Reporting at The Library and Archives Service of South Sulawesi Province - Asyiah, Nur; wati, Darma; Satria, Yudi (Candela Edutech Indonesia, 2025)
The Objectives – This study aims to analyze the influence of tax knowledge, tax perception, and their simultaneous effect on the tax reporting compliance of employees at the Library and Archives Service of South Sulawesi Province. The Methods/approaches – This study uses a quantitative descriptive approach. The data used consist of instruments in the form of questionnaires, which are designed in such a way as to be able to collect relevant and appropriate information regarding the influence of tax knowledge and perceptions on tax reporting compliance at the Library and Archives Service of South Sulawesi Province. Yhe data are then analyzed using several tests, such as validity test, reliability test, classical assumption test, hypothesis test, and multiple linear analysis. The Results – The result show that the influence of tax knowledge and tax perception, as a partial and simultaneous effect on the tax reporting compliance of employees at the Library and Archives Service of South Sulawesi Province. The Research Implications – This study is expected to provide practical insights for the Library and Archives Service of South Sulawesi Province and enrich academic references on tax reporting compliance.